The effect of estrogen hormone on premenstrual syndrome (PMS) occurrences in teenage girls at Pesantren Darul Arqam Makassar - Nur Indah Noviyanti; Gusriani; Ruqaiyah; Nasrudin A. Mappaware; Mardiana Ahmad (Elsevier, 2021)
Objective: PMS symptoms can include anxiety, quick temper, excessive strain on the breasts, increased or decreased appetite, nausea, vomiting, acne, low back pain, to faint. This study aimed to determine the effect of estrogen hormone in Adolescent Girls who experienced premenstrual syndrome at Darul Arqam, Makassar. Methods: The research design used the cross-sectional approach using the purposive sampling technique to get the samples of female teenagers who had PMS and another 25 samples of female teenagers who did not have PMS. The respondent who had experienced PMS filled in the daily diary sheets, did the blood taking of five ccs and underwent the examination of estrogen level using ELISA method. The study was conducted for three months, and the data were analyzed using the Mann-Whitney U test. Result: The research result indicated that the mean value of estrogen hormone in adolescent girls who experienced PMS was 148.32 pg/ml higher than the female teenagers who did not experience PMS of 98.00 pg/ml. The analysis result indicated that Ha was accepted, and H0 was rejected since the mean value in PMS teenagers was higher compared to the non-PMS teenagers with the value of p = 0.000 < α = 0.05. This result showed a significant effect of estrogen hormone in adolescent girls who experienced PMS compared to those who did not experience PMS. The adolescent girls who experience mild PMS with the mean value of estrogen hormone were 130.73 pg/dl, while those who experienced severe PMS of 162.14 pg/ml. Conclusion: It was found that the value of p = 0.000 < α = 0.05, which indicated that there was a significant effect of the levels of estrogen hormone between the non-PMS, mild PMS, and severe PMS.